Kant on morality, humanity, and legality: practical dimensions of normativity - Lyssy, Ansgar; Yeomans, Christopher (2021)
1.Introduction: Dimensions of Normativity -- 2. ‘Why be moral?’: How to take the question seriously (and why) from a Kantian perspective’ -- 3. Deceptive unity and productive disunity: Kant’s account of situated moral selves -- 4. It’s All About Power: The Deep Structure of Kant’s Categorical Imperative and its Three Formulations -- 5. Categorical Imperative and Human Nature, by Oliver Sensen -- 6. Motivating Humanity -- 7. Humans-Only Norms: An Unexpected Kantian Story -- 8. Beyond our given nature: Kant on the inviolable holiness of humanity -- 9. How Common is Common Human Reason? The Plurality of Moral Perspectives and Kant’s Ethics -- 10. The Philosopher’s Medicine of the Mind: Kant’s Account of Mental Illness and the Normativity of Thinking -- 11. “Eleutheronomy”: The Esoterically Political Character of Kant's Practical Philosophy -- 12. Kant and Privacy -- 13. Kant and the Provisionality of Property. .
This volume grew out of an identically titled conference at Purdue University on February 19-21, 2018
Keywords: Konferenzschrift -- 19.02.2018-21.02.2018 -- West Lafayette, Ind.